Fire trucks - Greve, Meg (Starting out, 2025)
"Fire trucks will introduce budding book learners to a noisy, colorful world with this new Starting Out title. Colorful photos, labeled diagrams, 'Make a Noise' section, glossary, and more ignite a passion for learning"--